Determinação de chumbo em águas por Espectrometria de absorção atômica com geração de Hidretos em um sistema de análise por injeção em fluxo - Carrijo, Jane Ferreira Neves (2001)
A method was developed for determination of lead by Atomic Absorption Spectrometry- Hydride Generation in Flow Injection Analysis. The flow injection system was operated in the merging zones configuration, where sample and reagent are simultaneously injected into two carrier streams, tartaric acid and water, respectively. There were difficulties with lead hydride formation, namely the low stability of the volatile hydride. therefore. an oxidant must be used to determine lead by this technique. For separation of lead hydride a continuous gas-liquid separator was used.The liquid phase flows to a free-running drain while the gaseous phase was purged by nitrogen into the atomization cell. The optimum conditions for the generation of lead hydride were established as: sample and reagent injected volume of 100 pL, 3.0 % (m/v) solution of sodium tetrahydroborate, 8.0 % (m/v) of ammonium peroxodisulfate as oxidizing agent, and 0.5 % (m/v) tartaric acid, cell temperature of 960 °C, flow rates of 2.8 mL min'1 for tartaric acid and tetrahydroborate Solutions and a flow rate of 50 mL min'1 for the carrier gas ( N2). Many elements cause interferences in this technique in gaseous and liquid phases. It was found that Ni (11), Cu (II), Al (III), Zn (II), Cd (II), Co (II), Mn (II), Fe (III), Hg (II), Sb (III), As (III), Se (IV) and Te (IV) cause signal reductions for lead of at least 10 %. Under the optimum experimental conditions, the detection limit, defined as three times the standard deviation of the blank measurement, was found to be 0,31 ng mL'1. The relative standard deviation of 3.2 % for 0.1 mg L'1 of Pb (II). The method was shown to be satisfactory for determination of traces lead in water samples (natural and certificate).